Statistical Analysis of the Verbs of Speaking заявить – заявлять (Announce – Proclaim) in News Texts of Electronic Media - H.G. Sheykhi (Ученые записки Казанского университета: Серия Гуманитарные науки)
According to the Russian National Corpus, the verbs заявить – заявлять (announce – proclaim) belong to the lexical-semantic group of verbs of oral communication and occur most frequently in mass media. This paper presents a statistical analysis of the functioning of the above-stated verbs in 1000 news texts of Russian electronic media (vesti.ru, 1tv.ru, izvestia.ru, rg.ru, ria.ru, top.rbc.ru, regnum.ru, echo.msk.ru, inosmi.ru, and tvc.ru) taken as the empirical basis of the study. It has been proven that the verbs function in the language of media not only in sentences with either direct or indirect speech, but also in simple extended sentences. The study has aimed to show, based on the discourse dynamics, the functioning specifics of the verbs of speaking заявить – заявлять, which are included in the lexical-semantic group of verbs of oral communication (with the base verb сообщить (report)) in news texts of electronic media. Data obtained from the dictionaries and our observations of the verbs заявить – заявлять show that they are used in electronic media in the meaning of “report or inform about something”. These verbs emphasize one of the semes relevant to the situation of communication, i.e., “сообщить”, and implement additionally acquired semantic features “свидетельствовать” (witness), and “высказываться” (speak out), as a consequence of the interaction of values in media texts. Apparently, this is due to the fact that the verbs заявить – заявлять are anthropocentric and characterize the action as the process of speaking in terms of its types, the concrete-actual one for the perfective verb заявить and the concrete-process one for the imperfective заявлять.